2008
DOI: 10.1063/1.2924288
|View full text |Cite
|
Sign up to set email alerts
|

Line defects of M-plane GaN grown on γ-LiAlO2 by plasma-assisted molecular beam epitaxy

Abstract: The edge and threading dislocations of M-plane GaN epilayers grown on γ-LiAlO2 have been studied by high-resolution transmission electron microscope. We found that edge dislocations were grown in [11¯00] direction while threading dislocations were generated along a1 or −a2 axes. We also observed a single stacking fault in the M-plane GaN epilayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
(19 reference statements)
3
10
0
Order By: Relevance
“…The micrographic images of the sample showed that the 2D M-plane GaN epi-film was developed along with the lateral orientation [ 1 1 ¯ 2 0 ] GaN // [0 0 1] LAO , while the 3D c-plane GaN hexagonal microdisks were grown atop an anionic hexagonal basal plane of LAO. The two-orientation growth of GaN nanopillars on the LAO substrate has been reported in our previous papers [13,14]. Figure 2(c) shows that the neck of contact area between the GaN microdisk and the LAO substrate is small (e.g.…”
Section: Characteristics Of Gan Microdiskssupporting
confidence: 60%
“…The micrographic images of the sample showed that the 2D M-plane GaN epi-film was developed along with the lateral orientation [ 1 1 ¯ 2 0 ] GaN // [0 0 1] LAO , while the 3D c-plane GaN hexagonal microdisks were grown atop an anionic hexagonal basal plane of LAO. The two-orientation growth of GaN nanopillars on the LAO substrate has been reported in our previous papers [13,14]. Figure 2(c) shows that the neck of contact area between the GaN microdisk and the LAO substrate is small (e.g.…”
Section: Characteristics Of Gan Microdiskssupporting
confidence: 60%
“…The slip of Co(OH) 2 closepacked plane (001) induces the partial dislocation of Co 3 O 4 close-packed plane {111}. Understandably, there is an edge dislocation corresponding to extra (400) half-plane atoms from the [011] direction view [26,27]. The HRTEM images trace the series of edge dislocations, showing lattice distortions of a given red region (Figures 2c, S4c and e).…”
Section: Resultsmentioning
confidence: 98%
“…The two-orientation growth of GaN nanopillars on LAO substrate has been reported in our previous papers. 15,16 In this paper, we applied the two-orientation growth to the M-plane InN film and 3D c-plane InN hexagonal thin disks on LAO substrate with GaN and InGaN buffer layers. The crystal structure of the sample was characterized by the high-resolution X-ray diffraction (XRD) (Bede D1) measurements and showed in Fig.…”
Section: Analyses and Resultsmentioning
confidence: 99%